Report of a germline double heterozygote in MSH2 and PALB2 - Konstantinos Agiannitopoulos; Eirini Papadopoulou; Georgios N. Tsaousis; Georgia Pepe; Stavroula Kampouri; Eleni Patsea; George Lypas; George Nasioulas (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background Carriers with pathogenic variants in MSH2 have increased risk to develop colorectal, endometrium, ovarian, and other types of cancer. The PALB2 is associated with breast, ovarian, pancreatic, and prostate cancer. We describe the case of a 42‐year‐old female diagnosed with endometrial cancer at the age of 42 years with a strong family history of colorectal cancer, which was referred to our private diagnostic laboratory for genetic testing. Methods In this study, we performed next‐generation sequencing (NGS) using an amplicon based 26 genes panel. The presence of multi‐exonic copy number variations (CNVs) was investigated by computational analysis and Multiplex Ligation‐dependent Probe Amplification (MLPA). Results A gross deletion of the genomic region encompassing exons 11–16 of the MSH2 and the loss‐of‐function variant c.757_758delCT, p.(Leu253Ilefs*3) in the PALB2 were identified in the proband. Conclusions Multigene analysis using NGS technology allows the identification of pathogenic variants in genes that would normally not be tested based on the patient diagnosis. In our case these results explained not only the personal and/or family history of cancer but also allowed the surveillance for prevention of other cancer types. Moreover, the detection of large genomic rearrangements should be routinely included in hereditary cancer testing.